Assessment of the factors contributing to the lack of agricultural mechanization in Jiroft, Iran - Gavgani Mahdi Sabati; Mohammadzamani Davood; Par-Shokohi Mohamad Gholami (Open Agriculture, 2022)
Agriculture and its development are the foundations of development in Iran as a developing country. So, this sector can be regarded as the foundation of economic and social development. The capabilities of the agriculture sector are limited, and its efficiency is trivial because of neglecting agricultural development and depriving this sector of real functional supports instead of slogans. The transformation of agriculture to a developed, dynamic, and efficient environment depends not only on appropriate climate and natural resources but also on human resource development in the relevant sector. Hence, in the present study, the causes of the underdevelopment of mechanization in rural areas of Jiroft which has a significant contribution to agricultural production in the area are investigated. Library and field methods have been used to collect information. The statistical population includes 1,324 farmers in Jiroft villages. According to Cochran’s formula, in order to complete the questionnaires, the required quantity as the sample was about 300 farmers. To determine the validity of the content, the experts used Cronbach’s alpha (0.81) to verify the reliability of the instrument. In the present study, the collected data were analyzed by statistical package of Social Sciences 22 and LISREL9 using Pearson correlation through exploratory and confirmatory factor analysis. The results of exploratory factor analysis showed that five factors, Supportive – research oriented and promotional, market and product, technical and technological, and cultural-social, respectively, were 19.9, 18.6, 14.5, 10.4, and 7.3 percent of the variance. Creating a national document in the field of sustainable development in agriculture, codification of supportive policies, and required laws for this sector are very impressive to improve the process of agricultural mechanization development in Jiroft.